Evaluasi Implementasi Sistem Informasi Manajemen Rumah Sakit (SIMRS) di Pelayanan Rawat Jalan RSUD dr. Gondo Suwarno Ungaran Menggunakan Metode Unified Theory of Acceptance and Use of Technology (UTAUT) - Setya - Wijayanta (Jurnal Rekam Medis dan Informasi Kesehatan, 2022)
RSUD dr Gondo Suwarno Ungaran has used the SIMRS application in every unit, including the medical record section, but there are problems that arise in the application of the system, namely the use of the system is still low on sustainable information systems and there are still staff who do not know and understand in utilizing the Hospital Management Information System. In outpatient services there is often duplication of data and inaccuracies in patient data. The research method used is quantitative research using a survey approach and analyzed using SmartPLS software. This evaluation uses the UTAUT method. The results of this study are: The effect of the PE variable on BI has a parameter coefficient value of 0.260 and a tstatistic value of 1.169*. The effect of the EE variable on BI has a parameter coefficient value of 0.038 and a tstatistic value of 2.027 *. The effect of the SI variable on BI has a parameter coefficient value of 0.089 and a statistical value of 1.795*. The effect of the FC variable on BI has a parameter coefficient value of 0.260 and a tstatistic value of 2.217*. The conclusion of this study is that the independent variables (EE, SI and FC) have a positive and significant effect on the dependent variable (BI), while the variable (PE) has a positive but not significant effect. It can be seen that business expectations, social influences, and facilitating conditions are factors that must be improved because these factors affect officers in using SIMRS. Recommendations for improvement that have been proposed are: To develop (upgrade) the SIMRS application. Perform interoperability/integration of SIMRS with several service units/sections and other applications. Conduct socialization and provide training to officers in the use of SIMRS.